2013
DOI: 10.1002/2013ja019195
|View full text |Cite
|
Sign up to set email alerts
|

Height‐dependent energy exchange rates in the high‐latitude E region ionosphere

Abstract: [1] The statistical properties of the altitude profiles of the different energy transfer rates in the auroral ionosphere are studied by using the European Incoherent Scatter radar measurements in Tromsø (67 ı cgmLat). Aikio et al. (2012) found that during active conditions, winds reduce the height-integrated Joule heating rates in the evening but enhance them in the morning. Here we show that the reduction in the evening takes place close to and above the peak altitude of Joule heating, so that the Joule heati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 24 publications
(67 citation statements)
references
References 48 publications
5
61
1
Order By: Relevance
“…Above 125 km, the wind direction is rather constant with altitude, but the magnitude increases. Then a difference even less than 90° between the wind and plasma flow directions can produce an enhancement in Joule heating as indicated by the model calculations by Cai et al [].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Above 125 km, the wind direction is rather constant with altitude, but the magnitude increases. Then a difference even less than 90° between the wind and plasma flow directions can produce an enhancement in Joule heating as indicated by the model calculations by Cai et al [].…”
Section: Resultsmentioning
confidence: 99%
“…Even though the Joule heating rate Q J is integrated over altitude and the wind velocities depend on altitude [see, e.g., Aikio et al , ], this figure provides some understanding for the effect of winds presented in Figure . Furthermore, Cai et al [] showed that the wind direction changes typically very slowly above this altitude.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations